2017
DOI: 10.1177/1040638717742435
|View full text |Cite
|
Sign up to set email alerts
|

Gangrenous dermatitis in chickens and turkeys

Abstract: Gangrenous dermatitis (GD) is a disease of chickens and turkeys that causes severe economic losses in the poultry industry worldwide. Clostridium septicum, Clostridium perfringens type A, and occasionally Clostridium sordellii are considered the main causes of GD, although Staphylococcus aureus and other aerobic bacteria may also be involved in some cases of the disease. GD has become one of the most significant diseases of commercial turkeys in the United States. Several infectious and/or environmental immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 65 publications
(201 reference statements)
1
30
0
1
Order By: Relevance
“…GD is commonly observed in broilers that are closer to market age (>35d) and is associated with increased condemnation rates and downgrades of carcasses at slaughter [ 128 ]. With prevalence and severity of GD increasing in the US, these downgrades will continue to increase production losses [ 132 ].…”
Section: C Perfringensmentioning
confidence: 99%
“…GD is commonly observed in broilers that are closer to market age (>35d) and is associated with increased condemnation rates and downgrades of carcasses at slaughter [ 128 ]. With prevalence and severity of GD increasing in the US, these downgrades will continue to increase production losses [ 132 ].…”
Section: C Perfringensmentioning
confidence: 99%
“…In addition, other microorganisms including Streptococcus spp. and Staphylococcus aureus have also been identified as potential agents of disease (5,8,9). Of significant interest to the current study is the view that E. coli is an infrequent cause of cellulitis in turkeys (9).…”
Section: Introductionmentioning
confidence: 96%
“…and Staphylococcus aureus have also been identified as potential agents of disease (5,8,9). Of significant interest to the current study is the view that E. coli is an infrequent cause of cellulitis in turkeys (9). Damage to tissues as a result of cellulitis often have their origin as a result of a trauma or injury to the bird and studies have demonstrated the importance of quality litter that is less likely to cause trauma as well as the microbiome of the litter which has the potential to affect skin health in injured or compromised birds.…”
Section: Introductionmentioning
confidence: 99%
“…Sci. 2020, 7, 54 2 of 11 also be spread via the bloodstream resulting in synovitis, chondronecrosis with osteomyelitis, arthritis, and endocarditis [7][8][9].…”
Section: Introductionmentioning
confidence: 99%